Adherence to Home-based Neuro-rehabilitation Exercise program in Stroke survivors (Bangladesh Journal of Medical Science, 2021)
Background:Post discharge, Home-based exercise program (HEP), prescribed by physiotherapistis an integral part, to plan effective stroke rehabilitation, with the intended goal of maintainingfunctional motor performance and enhancing functional progress.Earlier studies have shown thatmany factors attribute to adherence and barriers for structured group based exercise program.Objective: This study was designed to identify the factors in stroke subjects, which mayinfluence the adherence and barriers to individually tailored HEP post-discharge, in strokesubjects.Method: An analytical cross-sectional study, with non-random sampling, consistingof first onset stroke subjects who had received acute stroke rehabilitation from tertiary carehospitals. Post-discharge, seventy-four participants were followed up and their responses relatedto adherence and barriers to the prescribed HEP by administering a self-reported adherence to home exercise questionnaire.Results: 63.5% were adherent and 36.5% were non-adherent toHEP, among 74 subjects. The adherent group had performed exercises for at least 5-6 times in aweek, for 31-45 minutes each day. Intrinsic factors related to self-efficacy and perceived level ofanticipated recovery had found an association with adherent and non-adherent groups.The mostcommon barriers for adherence to HEP were fear of fall or injury and fatigue for both adherent and non-adherent subjects.Conclusion: This present study helped to put an insight, onto sociodemographicand intrinsic factors, with the level of adherence and to identify the barriers foradherence to individually tailored HEP.Bangladesh Journal of Medical Science Vol.20(1) 2021 p.145-153